Advertisements
Advertisements
प्रश्न
If y = (sec-1 x )2 , x > 0, show that
`x^2 (x^2 - 1) (d^2 y)/(dx^2) + (2x^3 - x ) dy/dx -2 = 0`
उत्तर
y = ( sec-1 x)2
`dy/dx = 2 (sec^(-1) x) 1/ (xsqrt(x^2 - 1))`
`x sqrt(x^2 - 1 ) dy/dx = 2 sec^(-1) x`
Again differentiating both sides
`x sqrt(x^2 -1) (d^2 y )/(dx^2) + (dy)/(dx) [sqrt(x^2 - 1 ) +(x^2)/ sqrt(x^2 - 1) ] = (2 xx 1 ) /(x sqrt (x^2 - 1))`
`x sqrt(x^2 -1) (d^2 y )/(dx^2) + (dy)/(dx) ((x^2 - 1 + x^2)/ sqrt(x^2 - 1) ) = 2/(x sqrt (x^2 - 1))`
`[ x (x^2 -1) (d^2 y )/(dx^2) + (dy)/(dx)(2x^2 - 1)] 1/sqrt(x^2 - 1 ) = 2/( x sqrt(x^2 - 1))`
`x^2(x^2 - 1) (d^2y)/(dx^2) + x(2x^2 - 1 ) (dy)/(dx) = 2 `
`x^2(x^2 - 1) (d^2y)/(dx^2) + x(2x^3 - x ) (dy)/(dx) - 2 = 0`
Hence proved.
APPEARS IN
संबंधित प्रश्न
Differentiate `cos^-1((3cosx-2sinx)/sqrt13)` w. r. t. x.
If `y=sin^-1(3x)+sec^-1(1/(3x)), ` find dy/dx
Differentiate `tan^(-1)(sqrt(1-x^2)/x)` with respect to `cos^(-1)(2xsqrt(1-x^2))` ,when `x!=0`
if `y = sin^(-1)[(6x-4sqrt(1-4x^2))/5]` Find `dy/dx `.
Find `dy/dx` in the following:
`y = sin^(-1) ((1-x^2)/(1+x^2)), 0 < x < 1`
Find `dx/dy` in the following:
`y = cos^(-1) ((2x)/(1+x^2)), -1 < x < 1`
Find `dy/dx` in the following:
`y = sin^(-1)(2xsqrt(1-x^2)), -1/sqrt2 < x < 1/sqrt2`
Find `dy/dx` in the following:
`y = sec^(-1) (1/(2x^2 - 1)), 0 < x < 1/sqrt2`
Differentiate w.r.t. x the function:
`cot^(-1) [(sqrt(1+sinx) + sqrt(1-sinx))/(sqrt(1+sinx) - sqrt(1-sinx))]`, ` 0 < x < pi/2`
If `sqrt(1-x^2) + sqrt(1- y^2)` = a(x − y), show that dy/dx = `sqrt((1-y^2)/(1-x^2))`
Find the approximate value of tan−1 (1.001).
If y = cos (sin x), show that: `("d"^2"y")/("dx"^2) + "tan x" "dy"/"dx" + "y" "cos"^2"x" = 0`
If y = sin-1 x + cos-1x find `(dy)/(dx)`.
If `log (x^2 + y^2) = 2 tan^-1 (y/x)`, show that `(dy)/(dx) = (x + y)/(x - y)`
The function f(x) = cot x is discontinuous on the set ______.
Trigonometric and inverse-trigonometric functions are differentiable in their respective domain.
`lim_("x" -> -3) sqrt("x"^2 + 7 - 4)/("x" + 3)` is equal to ____________.
`lim_("x"-> 0) ("cosec x - cot x")/"x"` is equal to ____________.
If `"y = sin"^-1 ((sqrt"x" - 1)/(sqrt"x" + 1)) + "sec"^-1 ((sqrt"x" + 1)/(sqrt"x" - 1)), "x" > 0, "then" "dy"/"dx"` is ____________.
The derivative of sin x with respect to log x is ____________.
The derivative of `sin^-1 ((2x)/(1 + x^2))` with respect to `cos^-1 [(1 - x^2)/(1 + x^2)]` is equal to